Pengaruh PENGARUH DEWAN KOMISARIS INDEPENDEN, UKURAN PERUSAHAAN, DAN KEBIJAKAN DIVIDEN TERHADAP NILAI PERUSAHAAN INDEKS KOMPAS 100 - Yuslinda Nasution; Rani Dyah Setyowati (Fakultas Ekonomi dan Bisnis Universitas Satya Negara Indonesia, 2023)
The purpose of this research is to ascertain how the Independent Board of Commissioners, Company Size, and Dividend Policy affect Company Value. Companies that are Kompas100 Index members that are listed on the Indonesia Stock Exchange in 2020 make up the population. 46 busnesses were used as samples in this research, which used the Purposive Sampling method. Analytic method used is multiple linear regression by using SPSS 25. The results of this study state that the results of simultaneous testing of the Independent Board of Commissioners, Company Size, and Dividend Policy Affect the Company's Value. The Independent Board of Commissioners and the Dividend Policy affects the Value of the Company, the Size of the Company does not affect the Value of the Company.